Absurdity in the Early 21 Century - Jurgens, Francois (Department of Philosophy, 2014)
This essay argues against contemporary theorists who claim that the concept of Absurdity that flourished in Western Europe in the 1940s is now of purely historical interest. It is argued instead that while it is important to locate the concept of Absurdity in an appropriate historical context, people living in the early twenty-first century are, in fact, living within an historical period that makes the experience, and thus the concept, of Absurdity relevant again. While Absurdity in the 1940s involved a loss of certainty due to the role the Second World War played in undermining secular and religious beliefs, Absurdity in the twenty-first century involves a loss of certainty due to intense exposure to alternative points of view. This loss of certainty means that when one's typical point of view is brought into relief by an atypical perspective, one struggles to reaffirm one's typical perspective. This robust clash of perspectives strikes at the heart of the way in which we understand the world and ourselves, forming part of the experience that has come to be known as Absurdity. If the analysis of Absurdity that is offered in this essay is correct, then Absurdity is best understood as a personal epistemological condition, rather than a universal metaphysical condition that affects all people simply in virtue of their being human.